The Comparative Analysis of Social Inequality and Alienation in A Short Happy Life of Conat and The Garden Party Using Marxism - Odelia, Risca Jovita; Bunadi, Stefanie Bunadi; Tamtama, Rafael Aglis Ariya; Kriswanto, Dian Widya; Sriastuti, Anna (Faculty of Arts and Education, 2024)
The analysis combines two stories, The Short Happy Life of Conat by Mochtar Lubis and The Garden Party by Katherine Mansfield. The aim of this analysis is to examine inequality or class distinction and exploitation, and to explore the theme of alienation between the main characters of both stories. Using Marxist theory, this analysis highlights social and economic philosophy and relates it to the main characters, showing how they navigate their economic conditions, whether upper class or lower class. Through a Marxist lens, the study examines how Conat and Laura experience different forms of alienation as a result of their socio-economic conditions. Conat, a trishaw driver, faces alienation from both the product of his labor and the labor process itself, reflecting Karl Marx's theories of alienation in a capitalist society. Laura, on the other hand, experiences a form of alienation from herself, where her family's capitalistic priorities overshadow empathy and human connection. Despite their different contexts and backgrounds, both characters illustrate the pervasive impact of alienation within their respective societies. Keywords: alienation, exploitation, Karx Marx, Marxist theory, social inequality